MEKANISME DAN PROSEDUR DOKTRIN BUSINESS JUDGEMENT BERDASARKAN UNDANG-UNDANG NO. 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Nadia Rahma Dani,; Admiral, (Proceeding International Conference on Social Sciences, 2026)
The Business Judgment Rule doctrine is a principle of corporate law that provides protection to directors from legal liability for business decisions made in good faith, with due care, and in the best interest of the company. In the Indonesian context, this doctrine gains its legal basis through Law No. 40 of 2007 concerning Limited Liability Companies (UUPT), particularly Article 97 paragraph (5), which discusses the liability of directors for losses suffered by the company if they are found guilty or negligent in carrying out their duties based on the Business Judgment Rule. Business decisions made by members of the board of directors cannot be questioned, challenged, or annulled by the court or shareholders. Directors cannot be held liable for the outcomes of business decisions they make, even if those decisions are deemed incorrect, except under certain circumstances. The main issues explored in this research are: first, how the Business Judgment Doctrine is applied in terms of legal certainty, justice, and utility in Indonesia; and second, how the Business Judgment Doctrine is applied in practice within Indonesian corporate law. The writing method used in this study is a descriptive-analytical method within the framework of a normative juridical approach. This method is carried out by systematically describing and analyzing laws and regulations, legal doctrines, and theories related to the responsibility of directors for losses in limited liability companies as regulated in Law No. 40 of 2007 concerning Limited Liability Companies. The results of the study show that the application of the Business Judgment Rule in Indonesia is still partial and lacks a standardized mechanism for assessing “good faith,” “due care,” and the “best interest of the company.” Although the UUPT has adopted the substance of this principle, there are no explicit procedural guidelines regarding the process of proving and assessing directors’ liability. As a result, interpretations of this doctrine still depend on the subjective judgment of judges and are not yet consistent in corporate judicial practice.